Gambaran Pengetahuan Anak terhadap Bullying di SD Negeri 23 Pasir Sebelah Kota Padang - Sari Indah Kesuma; Meri Neherta; Lili Fajria (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Bullying is a serious and threatening problem for Indonesian children. Bullying incidents that last a long time will have an impact on victims of bullying, both physically, psychologically, and socially. This bullying incident if it lasts for a long time will cause physical, psychological, and social impacts. Children will experience mental disorders such as being sensitive, feeling angry, depression, low self-esteem and anxiety, physical injury, wounds, bruises, lack of confidence. and reduce physical ability in social. The purpose of this study was to determine the description of children's knowledge of bullying at SD Negeri 23 Pasir Sebelah Padang City. This research is a quantitative research with descriptive analysis design. The results in this study obtained good knowledge of 28 people (40.0%) and lack of knowledge as many as 15 people (21.4%). It can be concluded that the knowledge of bullying in SD Negeri 23 Pasir Sebelah children is in the good category. It is hoped that further research will be carried out regarding the observation of children's actions on the incidence of bullying.